A novel approach to prepare graphite nanoplatelets exfoliated by three-roll milling in phenolic resin for low-carbon MgO-C refractories. Issue 9 (August 2023) - Liu, Mingqiang; Huang, Juntong; Meng, Hongtao; Liu, Cheng; Chen, Zhi; Yang, Huiyong; Feng, Zhijun; Li, Xibao; Luo, Ruiying; Huang, Zhaohui; Zhang, Shaowei
Abstract: Development of nano carbon containing magnesia graphite refractories to reduce the total carbon content is urgently required for application of low carbon steel smelting. In this work, a novel approach to prepare graphite nanoplatelets (GNPs) by exfoliating flake graphite (FG) in the medium of phenolic resin (PF) via three-roll milling, and the as-prepared GNPs/PF mixtures were used in MgO-C bricks to develop a novel low carbon magnesia-carbon refractories (LCMCRs). The results show that with the increasing of exfoliation times, the FG was constantly thinned, and the production of GNPs had thicknesses of 10–20 nm after exfoliation for 16 times. As a carbon source for LCMCRs, the GNPs and/or GNPs/PF mixture with 2 wt. % carbon could improve the comprehensive performance of the LCMCRs, including the higher cold crushing strength and hot modules of rupture, the better oxidation resistance and slag corrosion resistance. The GNPs continue uniformly dispersed and wrapped with magnesia aggregate, playing an importance role and positive impaction on the corrosion resistance of refractories.